Analisis Faktor Motivasi Wisatawan Generasi Z Berkunjung Ke Daya Tarik Wisata Danau Tarusan Kamang Kabupaten Agam (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
Tourist motivation is an important element because it is the driving force for someone to do tourism activities. The younger generation has more potential in traveling because they are more active in knowing tourist attractions. The results of the pre-survey show that the Tarusan Kamang lake in Agam Regency is one of the favorite tourist attractions of generation Z. The purpose of this research is to find out what factors motivate and what factors dominate generation Z tourists visiting a tourist attraction. The method used in this research is descriptive quantitative. Analysis testing uses data tabulation, data description and factor analysis. Based on the results of this study, there are 4 new factors that motivate  generation Z tourists to visit  a tourist attractions, namely relaxation, amenities, location, educational opportunity.